2015
DOI: 10.1007/s00707-015-1541-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of regions of irregular and chaotic vibrations of an asymmetric rotor supported on journal bearings to structural parameters

Abstract: Rotating elements supported on journal bearings are widely encountered structures in engineering practice. Most commonly, these are asymmetrically manufactured and loaded rigid rotors transmitting torque and carrying transverse as well as axial forces. Nowadays, despite high operational demands and high rotational velocities, such systems are still expected to exhibit stable working, even in the presence of small assembly deviations, light unbalance or external disturbances. The surrounding environment of a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is concluded that the crack depth and the stator stiffness have an important role in both the system instability and oscillation amplitudes. Przybylowicz et al [12] studied the influence of the kinematic excitation on the asymmetric rotor numerically. ey showed that the proper design of both the system stiffness coefficient and damping parameter can eliminate the system's chaotic motion.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that the crack depth and the stator stiffness have an important role in both the system instability and oscillation amplitudes. Przybylowicz et al [12] studied the influence of the kinematic excitation on the asymmetric rotor numerically. ey showed that the proper design of both the system stiffness coefficient and damping parameter can eliminate the system's chaotic motion.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [1] incorporated PID control and robust model reference adaptive control (RMRAC) to realize the levitation control of Lorentz force-type self-bearing motors. Reference [2] analyzed regions of irregular and chaotic motion in the system of a rigid rotor supported in journal bearings. The adjustability of the viscoelastic parameters may be realized by incorporation of magnetorheological forces.…”
Section: Introductionmentioning
confidence: 99%
“…In one of early experiments in chaotic motion of rotor systems, Ehrich [2] observed period doubling routes to chaos in a rotor with dead-band nonlinearity. Up to now, many studies has been carried out in study of chaotic vibration in rotor-dynamics; for example chaotic responses due to rub-impacts in rotors has been studied in references [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]; the chaotic dynamics of rotors due to effects of bearing has been investigated in papers [18][19][20][21][22][23][24][25]. Most of these papers treated the rotor with strong nonlinearity.…”
Section: Introductionmentioning
confidence: 99%